PENGARUH PENERIMAAN DANA OTONOMI KHUSUS DAN TAMBAHAN DANA BAGI HASIL MIGAS TERHADAP BELANJA MODAL SERTA DAMPAKNYA PADA INDEKS PEMBANGUNAN MANUSIA KABUPATEN/KOTA DI ACEH - Cut Sri Hartati, Syukri Abdullah, Mulia Saputra. (Jurnal Akuntansi, 2016)
Abstract:Since it is designated as a special autonomy province, Aceh has received substantial funds by the central government, either the special autonomy fund and Gas Share Additional Funding. The local government can use these funds to develop infrastructure in various sectors in order to support the welfare of the community, one of which can be measured by the HDI (Human Development Index). The Regencies/Cities Authorities have budgeted a subtantial capital expenditure to the infrastructure development. The special autonomy issue associated with the community welfare measured with the HDI is, therefore, interesting to conduct a study. The purpose of this study was to examine and analyze the effect of the receipt of special autonomy and Gas Share Additional Fundingfunds toward the capital expenditures and their impact on Human Development Index in Districts/Municipalities in Aceh Province.This study is a hypothesis testing research by using path analysis to figure out the population data collected based on documents and reports that are made available from Bappeda (the Provincial Development Planning Agency)of Aceh, Directorate-General of Regional Fiscal Balance of the Ministry of Finance, and Central Bureau of Statistics of Aceh. The results of this study show that the funds allocated for the Aceh Province from Speacial Autonomy and Gas Share Additional Fundingschemes have positive effects both jointly and simultanously toward the capital expenditures of Districts/Municipalities in Aceh. Furthermore, the results also prove that the fundings and capital expenditures have positive effects either jointly or partially on the HDI of the Districts/Municipalities in the Aceh Province. For direct and indirect influences, it shows that the capital expenditures do not mediate the effect of special autonomy fund toward the HDI. Other results prove that the capital expenditures mediate the effect of Gas Share Additional Fundingto HDI.Keywords: Special Autonomy Fund, Gas Share Additional Funding, Capital Expenditure, Human Development Index (HDI), Community WelfarenAbstrack:Sejak ditetapkan sebagai daerah otonomi khusus (otsus), Aceh memperoleh dana daerah yang cukup besar, baik dari dana otsus maupun dari TDBH migas. Dengan dana yang besar tersebut dapat dimanfaatkan untuk melaksanakan pembangunan infrastruktur diberbagai sektor untuk dapat menunjang kesejahteraan masyarakat yang salah satunya dapat diukur dengan IPM. Untuk melaksanakan pembangunan infrastruktur tersebut, pemerintah Kabupaten/kota di Aceh telah menganggarkan belanja modal yang cukup besar. Oleh karena itu, isu otonomi khusus dikaitkan dengan tingkat kesejahteraan masyarakat yang diukur dengan IPM menjadi hal menarik untuk dilakukan penelitian. Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh penerimaan dana otonomi khusus dan TDBH Migas terhadap belanja modal serta dampaknya pada IPM kabupaten/kota di Aceh. Jenis penelitian ini merupakan hypothesis testing reasearch dengan menggunakan path analysis terhadap data populasi yang dikumpulkan berdasarkan dokumen dan laporan yang telah tersedia di Bappeda Aceh, DJPK Departemen Keuangan dan Badan Pusat Statistik (BPS) Aceh. Hasil penelitian membuktikan bahwa penerimaan dana otsus dan TDBH 2 Migas berpengaruh positif baik secara bersama-sama maupun secara parsial terhadap belanja modal kabupaten/kota di Aceh. Selanjutnya hasil penelitian juga membuktikan penerimaan dana otsus, TDBH Migas dan belanja modal berpengaruh positf baik secara bersama-sama maupun secara parsial terhadap IPM kabupaten/kota di Aceh. Untuk pengaruh langsung dan tidak langsung membuktikan bahwa belanja modal tidak memediasi pengaruh dana otsus terhadap IPM. Hasil lainnya membuktikan belanja modal memediasi pengaruh TDBH Migas terhadap IPM.Kata kunci: Dana Otsus, TDBH Migas, Belanja Modal, IPM, Kesejahteraan Masyarakat.